Measuring safety rating in construction project (case study) - Mohamad Hafizuddin, Mohd Bakhri (2017)
Accident on construction site is an issue that can affect the construction sector image. According to Department of Occupational Safety and Health(DOSH), accident rate have increased since year 2012 to 2015 which highly number increased 73 death cases in year 2012 to 140 cases in 2015. On the other hand, safety is the important part to concern to avoid increasing the number of death. Safety is to avoid worker from being harm, to protect the community or surrounding from exposed to dangerous, to provide a good and well arrangement material and work. This study focusing only construction in Malaysia, and the important issue of safety to counter the accident that increases every years. The reason of increasing the number of death is because contractor didn’t applied effectiveness current safety practice at the site as a guideline to reduce the number of accident happened. The project manager or contractor underestimate the importance be safe at site. Contractor and project manager do not awareness at the site by ignoring the correct procedure regulation act, assessment to be safe and performance at site working in safe place. The aim of the research is to view the effectiveness safety in construction works to counter the increasing number of death. The result can be done by studies on the current safety practice at the site and identify the safety assessment approach and to evaluate safety level performance. The safety can be achieved by implementation tightly procedure and knowledge in safety regulation.